Peran Komunikasi Antarbudaya dalam Mengatasi Hambatan Sosialisasi Program Pemerintah di Wilayah Multikultural - Putri ayu; Desi Romandani; Afifah Arum Wijayanti (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Culturally diverse regions face unique challenges in implementing government outreach programs. This study explores how intercultural communication can be an effective solution to address these barriers. The research was conducted through a case study of an inclusive education program in Papua. The results show that a participatory approach and local language adaptation increased the program's acceptance by the local community.